Ovarian Reserve after Laparoscopic Ovarian Cystectomy in Infertile Patients - Eslam Awad (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background:Ovarian reserve is the key target of infertility treatment; its accurate evaluation is extremely important for outcomes prediction of in-vitro fertilization [IVF].Ovarian cysts act as a common gynecological site that occurred in 6.6% of patients between twenty-five and forty years old. When its surgical removal is indicated, stripping the ovarian cyst wall by laparoscopic approach is the technique of choice. Aim of the Work: The present study was designed to evaluate ovarian reserve after laparoscopic ovarian cystectomy by using basal Follicular Stimulating hormone [FSH], Anti-Mullerian hormone [AMH], and Antral follicle count [AFC] as a marker for evaluation. Patients and Methods:This was an observational study which was conducted on infertile patients after laparoscopic ovarian cystectomy from the Obstetrics and Gynecology department Al-Azhar University hospital [New   Damietta] from October 2018 to last of November 2019. Results:AFC had been increased significantly post-cystectomy when compared to corresponding preoperative values [17.8±2.24 vs 5.57±3.16 respectively]. On the other side, both FSH and AMH significantly decreased after cystectomy when compared to preoperative values. These results are constant regardless of the type of the cyst, the surgical procedure, or its polarity.   Conclusion: The FSH and AFC levels increased after laparoscopic cystectomy for benign ovarian cysts, indicating significant ovarian damage post operatively.